Experimental and Optimization Study on the Sliding Force Monitoring and Early Warning System for High and Steep Slopes - Ligang Wang; ZhiGang Tao; ManChao He; Xiaocong Yang (Advances in Civil Engineering)
A series of high and steep slopes have been formed due to the deep exploitation of resources in open-pit mines across China. The stability of these high and steep slopes has become an essential factor affecting the efficient, safe, and sustainable development of deep mineral resources. Due to numerous problems such as constant resistance fluctuation and pipe jamming of the original sliding force monitoring system, leading to system failure, a series of improvements on the current monitoring systems were implemented. This specific work included a mechanical characteristics test of the anchor cable, improvement of the constant resistance structure, and measurement of the internal displacement of the slope. The communication mode and the software architecture of the system were also adjusted. This work significantly improved the overall performance of the sliding force monitoring and early warning system. The improvements performed in this research are systematically described to provide an example of good practice for other sites with similar features. The collected data show that the improved sliding force monitoring system can accurately reflect the whole process of landslide incubation. Moreover, the validity of the early warning criterion based on the sliding force is verified again using the field test.